1971
DOI: 10.1159/000178241
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis against Exophthalmos or its Progression in Newly-Treated Thyrotoxicosis

Abstract: Exophthalmos usually did not appear nor did pre-existent exophthalmos progress in thyrotoxic patients treated with desiccated thyroid in full replacement dosages, 2½ to 3 grains per day, simultaneously with thyroid blocking agent therapy, 131I administration, or thyroidectomy. Indeed, in most patients so treated, exophthalmos present prior to therapy of the hyperthyroidism decreased or disappeared. Our observations are consonant with the hypothesis that full replacement dosages of thyroid hormones s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Dandona et al (1981) tried plasmapheresis for the treatment of exophthalmos and reported it to be effective. Danowski et al (1971) suggested that prescription of adequate doses of thyroid hormone at the time of treatment of thyrotoxicosis is beneficial. The present study reports our results with steroid therapy, supervoltage orbital radiotherapy, plasmapheresis and thyroxine replacement therapy in 13 patients with moderately severe ophthlamopathy.…”
mentioning
confidence: 99%
“…Dandona et al (1981) tried plasmapheresis for the treatment of exophthalmos and reported it to be effective. Danowski et al (1971) suggested that prescription of adequate doses of thyroid hormone at the time of treatment of thyrotoxicosis is beneficial. The present study reports our results with steroid therapy, supervoltage orbital radiotherapy, plasmapheresis and thyroxine replacement therapy in 13 patients with moderately severe ophthlamopathy.…”
mentioning
confidence: 99%